Desenvolvimento de vetores de expressão reguláveis utilizando o promotor do gene da trealase ácida de metarhizium anisopliae - (:unkn) unknown (Universidade Federal do Pampa, 2015)
Metarhizium anisopliae is an entomopathogenic biocontrol fungus capable of infecting a wide range of arthropods, and a microorganism model for host-pathogen interaction studies. This fungus infects its hosts directly through the cuticle making use of a multifactorial process involving mechanical pressure and hydrolases secretion. In the infective process, upon reaching the hemolymph of the host, hyphae differentiate into oval cells (blastospores) which facilitate the spread of the fungus being the main source of carbon present in the hemolymph of insects is the disaccharide trehalose. Thus, to allow the use of trehalose as a nutrient, an important fungal hydrolase, acid trehalase (EC. 3.2.1.28), is secreted. In a genomic analysis, a putative ortholog of the gene encoding an acid trehalase (ATM1) was identified in M. anisopliae. However, there are few reports on studies with regulatory elements included in the promoter of these genes. It is suggested only that there must be evidence of catabolite repression by glucose and trehalose responsive elements. A promoter is considered to be regulated when dependent on environmental or genetic conditions to promote the induction or repression of gene mRNA synthesis succeeds. Inducible vectors are tools that enable the promoter regulation and allow better control of gene expression. To date, two homologous promoters have been described for M. anisopliae (PTef and PMa-icl), both considered constitutive nature in predefined conditions. The promoter from the acid trehalase has been described to regulate downstream gene expression induced only in the hemolymph and its regulated nature allows an optimization of the expression of genes of interest. Based on this, this paper aims to isolate the promoter region of the acid trehalase gene of M. anisopliae and develop potential vectors adjustable by carbon source. Different promoter fragments were isolated by PCR (1540, 750 and 500 bp) in order to identify the functional minimal promoter region of M. anisopliae acid trehalase and these were used in the construction of vectors for controlled expression of reporter genes (GFP - green fluorescent protein and yeCherry – red fluorescent protein) through successive cloning and subcloning techniques. After obtaining the constructs, these were integrated into the genome of M. anisopliae via agrotransformation mediated by Agrobacterium tumefaciens. The constructs were obtained successfully and there was a high rate of positive transformants isolated due to ectopic recombination in the fungus genome.
Keywords: Fungos; Trealose; Metarhizium anospliae; Trehalose; Fungus; Metarhizium anisopliae; CNPQ::CIENCIAS AGRARIAS